2013
DOI: 10.2174/1574888x11308030002
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterials and Scaffolds in Bone and Musculoskeletal Engineering

Abstract: In orthopaedic tissue engineering, scaffolds may be viewed as a substitute for the extra-cellular matrix. Factors that contribute to an ideal scaffold include strength, degradation rate, porosity, surface property and immune response.Scaffolds may be composed of natural or synthetic polymers, each with its advantages and disadvantages. Composite scaffolds are utilised to alleviate the inherent issues with natural polymers whilst maintaining its benefits as well. This article reviews biomaterials and scaffolds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Their disadvantages are quick loss of mechanical properties after implantation and potential toxicity. Synthetic materials also show a lower degree of biocompatibility, than the natural ones (Kosuge et al, ). Most commonly used synthetic polymers in AC regeneration include, poly(ethylene glycol) (PEG) and its derivatives, poly(Lactide‐co‐glycolide) (PLGA), and poly( l ‐lactic acid) (PLLA).…”
Section: Advanced Therapiesmentioning
confidence: 99%
“…Their disadvantages are quick loss of mechanical properties after implantation and potential toxicity. Synthetic materials also show a lower degree of biocompatibility, than the natural ones (Kosuge et al, ). Most commonly used synthetic polymers in AC regeneration include, poly(ethylene glycol) (PEG) and its derivatives, poly(Lactide‐co‐glycolide) (PLGA), and poly( l ‐lactic acid) (PLLA).…”
Section: Advanced Therapiesmentioning
confidence: 99%
“…Generally speaking, the degradation time of materials should match the production speed of the new tissue. Rapid degradation of the scaffold affects the adhesion of chondrocytes, while slow degradation hinders cells' proliferation and matrix secretion (Bettinger, 2011;Kosuge et al, 2013). From H & E staining and immunohistochemical staining results, we observed that chondrocytes cultured in hydrogel in vitro can grow and secrete extracellular matrix-collagen II.…”
Section: Discussionmentioning
confidence: 93%
“…Bone tissue engineering has been developing as a promising approach to regenerate bone defects where it can be implanted in vivo at the bone defect site, and a precise design of 3D scaffold is essential to effectively support and promote new bone tissue regeneration . Previously, we have shown that the physical and mechanical properties of methacrylated HA‐based hydrogels could be optimized through types and concentration of the chemical crosslinkers .…”
Section: Discussionmentioning
confidence: 99%